2018
DOI: 10.2478/picbe-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness of companies for digital transformation and creating a competitive advantage in the age of Industry 4.0

Abstract: One of the biggest challenges that organizations are facing today is finding the proper way to shape competitive advantages in the age of Industry 4.0. This digital revolution forces companies to face specific challenges. The main purpose of this paper is to identify key requirements for the creation of a competitive advantage in the age of Industry 4.0 [CA. 4.0] The second purpose is to evaluate the level of organizations' preparedness for Digital Transformation [DX]. Studies based on a literature review desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…The conducted analyses showed that the research of the above problems is generally quite universal and well known. However, the fact that they are usually conducted without mutual coincidence taken into account should be noted, i.e., the importance of CSR is investigated separately (i.e., [54,55,60,62,137,169]), the problems of cooperation and networking separately (i.e., [13,15,16,18]), aspects of co-creation separately (i.e., [13,27,28,47,137]), paradoxes and/or pathologies separately (i.e., [35,37,39,73,112]), or separately the problems of the importance, requirements, positive sides and threats of Industry 4.0 (i.e., [9,63,89,91,183]. Therefore, the base, developed for the needs of this article, aggregating "the paradoxes and areas of potential pathologies of co-creation in the age of Industry 4.0", may be considered a certain novelty, contributing to management studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conducted analyses showed that the research of the above problems is generally quite universal and well known. However, the fact that they are usually conducted without mutual coincidence taken into account should be noted, i.e., the importance of CSR is investigated separately (i.e., [54,55,60,62,137,169]), the problems of cooperation and networking separately (i.e., [13,15,16,18]), aspects of co-creation separately (i.e., [13,27,28,47,137]), paradoxes and/or pathologies separately (i.e., [35,37,39,73,112]), or separately the problems of the importance, requirements, positive sides and threats of Industry 4.0 (i.e., [9,63,89,91,183]. Therefore, the base, developed for the needs of this article, aggregating "the paradoxes and areas of potential pathologies of co-creation in the age of Industry 4.0", may be considered a certain novelty, contributing to management studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them are less and some of them are more accurate [85][86][87], which causes disorientation as to where an organization's strategic actions should be directed [88]. The decision is not made easier due to the increasing dynamics of changes and requirements from the market environment, e.g., the age of Industry 4.0 that has been in place for some time now [89]. The revolution that accompanies it strengthens the unparalleled, "unprecedented fusion" between digital, physical, and biological entities, which is the aim for social, economic, and environmental progress [90,91].…”
Section: The Age Of Industry 40 As a Context Of Building A Competitimentioning
confidence: 99%
“…Kagermarin et al [2] refer to the digitization of production and describe the vision of an intelligent factory, characterized by the networking of all production processes in order to operate interactively and to increase productivity and efficiency in the use of resources. Companies are facing increasing competition in their markets, leading managers to constantly seek new methods, approaches, and strategies to improve operational flexibility, efficiency, innovation, and responsiveness through an accurate control supported by 4.0 technologies [3,4]. The use of digital approaches anticipates the development and control of intelligent production systems by contributing, for example, to the control of production flow's behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A nation's competitiveness [9] is measured by the quality of its Human Resources and job competency. One of the efforts made at increasing these in Vocational High School was by giving competency certificate to the graduates through a professional certification institution [2].…”
Section: Introductionmentioning
confidence: 99%